Study of Factors Influencing Rice Farming Income : (Case Study: Kuta Jungak Village, Siempat Rube District, Pak-Pak Bharat Regency, North Sumatra Province) - Medi Lilis Wenny Nainggolan; Aditia Erick Cantona Simatupang; Jepri Padang (ITScience (Information Technology and Science), 2026)
This study aims to determine the production costs, the amount of revenue and income, feasibility, and factors that influence the income of rice farming in Kuta Jungak Village, Siempat Rube District, Pakpak Bharat Regency. The method of determining the research area was done intentionally (purposive), and the method of determining the sample was done by the Simple Random Sampling method, with a total of 45 rice farmers. The analysis methods used were cost analysis, revenue, income, Revenue Cost Ratio (R/C), and multiple non-linear regression. The results showed that the total production cost was Rp112,116,612, while the total revenue was Rp184,283,910, resulting in a total income of Rp72,167,298. The R/C ratio value of 1.64>1, which means that rice farming is feasible to pursue. The results of the study indicate that production factors such as land area, labor, seeds, fertilizer, pesticides, and selling price significantly influence rice farming income. Simultaneously, the variables of land area, labor costs, seed costs, fertilizer costs, pesticide costs, and selling prices significantly influence rice farming income. Partially, the variables of labor costs, seed costs, and fertilizer costs significantly influence income. Meanwhile, the variables of land area, pesticide costs, and selling prices do not significantly influence rice farming income. The coefficient of determination R2 is 0.340, which means that land area, labor, seeds, fertilizer, pesticides, and selling prices influence 34% of rice farming income. Other factors outside of this study influence the remaining 66%.